1356 Continuous Glucose Monitoring in Very Low Birthweight Preterm Infants on Full Enteral Feeds. (October 2012) - Riehle, E Mola; Staffler, A; Klemme, M; Schulze, A; Flemmer, AW
Abstract : Background: We previously observed hypoglycaemic episodes in preterm infants after achieving full enteral feeds and during a stable postnatal period. The purpose of this study was to prospectively determine subcutaneous glucose levels in this population. Methods: Preterm infants < 32wks gestational age were enrolled for continuous subcutaneous glucose monitoring over 72hrs in two cohorts: A: 500–999g (n=16); B: 1000–1500g (n=9). All infants were fed according to a standard feeding protocol where full feeds are provided at 150–180ml/kg/d of fortified EBM or premature formula at 110–135kcal/kg/d. Primary outcome was the frequency and quality of hypoglycaemic episodes within 72 hours, defined as tissue glucose < 2.5mmol/L. Results: 81.3% of the infants in A and 44.4% in B showed relevant glucose fluctuations during monitoring. Hypoglycaemic episodes occurred in 37.5% in group A, compared to 22.2% in group B. In group A 7% of infants showed glucose values below 1.7mmol/L. We also observed hyperglycaemic episodes (>8.3mmol/L) after feeds (A: 57%, B:17%), followed by rapid drops in both cohorts. Cumulatively, all hypo- and hyperglycaemic episodes lasted >60 min (16%), 35–60 min (21%), 10–30min (60%) and < 5min (3%) per patient. The main risk factors for glucose instability were gestational age and weight at trial. Conclusion: Otherwise stable, well developing former very low birth weight preterm infants are at risk for glucose instability, generally considered as unfavourable. It remains unclear whether this instability is likely to influence long-term outcome and whether continuous feeds are preventive.